Development of a Measure of Nociception for Patients With Severe Brain Injury. Issue 4 (April 2020) - Whyte, John; Poulsen, Ingrid; Ni, Pengsheng; Eskildsen, Marianne; Guldager, Rikke
Abstract : Objectives: Severe brain injury is often accompanied by painful comorbidities and by concurrent limitations in the ability to report pain. Assessment of nociception aids diagnosis and helps balance reduction in suffering with avoidance of sedating medications. Existing assessment methods confound patients' level of consciousness with the intensity of nociception, complicating pain assessment as consciousness evolves. We sought to develop a measure of nociception that is independent of the level of consciousness. Materials and Methods: We identified 15 behavioral and physiological items likely to be sensitive to nociception. We rated noncommunicative patients with traumatic brain injury in 4 different activities predicted to modulate nociception, on each of 2 days, one randomly chosen for acetaminophen administration. The level of consciousness and level of agitation were also measured. Rasch Analysis: Rasch analysis was used to assess item fit to an underlying dimension of nociception. Results: Five items that demonstrated poor fit to the dimension were removed. The 10 remaining items demonstrated acceptable fit. Scores were significantly influenced by activity and analgesic treatment and were largely independent of measures of consciousness and agitation. Accurate scores could be obtained in about 10 minutes and were robust to missing data. Discussion: The results provide evidence that the Brain Injury Nociception Assessment Measure (BINAM) is reliable and feasible to administer. It can assess the intensity of nociception largely independent of the level of consciousness. Further research is warranted on the impact of BINAM use on the care of patients with severe traumatic brain injury.